ANALISIS LAPORAN KEUANGAN TERHADAP EFEKTIFITAS PENILAIAN PERMOHONAN KREDIT PERBANKAN - Eka Dyah Setyaningsih (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
The bank must implement analyzing the financial statements which are owned by the company. The purpose of analyzing this is to look at what the effectiveness of the assessment of the credit application. The analysis of financial statements that will be made by the bank were assessed using Liquidity Ratio, Solvency Ratios and Profitability Ratios.Financial statement analysis techniques using liquidity ratios, solvency ratios and profitability ratios used by the bank to assess the financial condition of the company applying for credit. Analyzing these will describe the financial condition of the company which will be how much the effectiveness of the assessment of the credit application. This is done because the bank wants to know the rate of return of the company to the bank. Then the analysis is done by the bank before deciding on a loan application is accepted or rejectedThe data obtained through observation and documentation techniques. Analysis of the financial statements to obtain data as DEF and GHI berikunya company received credit for the analysis report perrmohonan keuanganya dlihat of liquidity, solvency and profitability showed a value above the average standard bank. JKL Company credit application is not accepted because it did not conform lower than standard bank Keywords : financial statements, the effectiveness of credit scoring